2006
DOI: 10.1007/bf02825481
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pediatric HIV in New Delhi

Abstract: HIV infection is an emerging reality in New Delhi. A clinically directed screening can help detect more cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 1 publication
1
6
2
Order By: Relevance
“…[4] Parthasarathy et al , reported a prevalence of 8.9% in 2006 in New Delhi. [3] However, prevalence in our study was 5.4%. This fall in seroprevalence may be attributed to the effectiveness of the Prevention of Parent to Child Transmission (PPTCT) program by NACO, which was started in 2002.…”
contrasting
confidence: 71%
See 1 more Smart Citation
“…[4] Parthasarathy et al , reported a prevalence of 8.9% in 2006 in New Delhi. [3] However, prevalence in our study was 5.4%. This fall in seroprevalence may be attributed to the effectiveness of the Prevention of Parent to Child Transmission (PPTCT) program by NACO, which was started in 2002.…”
contrasting
confidence: 71%
“…This is particularly true for India where the major mode of transmission is heterosexual contact. [3]…”
mentioning
confidence: 99%
“…18 In another study conducted by Parthasarathy et al at New Delhi, failure to thrive was observed to be 10% in seropositive cases, the disparity can be explained on the basis of small sample size in their study. 6 We observed by statistical analysis that the correlation between incidence of HIV and children who had failure to thrive was highly significant (p <0.001).…”
Section: Discussionmentioning
confidence: 82%
“…Parthasarath observed that 10% seropositive children had pulmonary tuberculosis, which was quite similar to our study. 6 In study conducted by Pol et al pulmonary tuberculosis was observed in 36.3% seropositive cases. 16 In another study, Shah et al observed that 38% seropositive children had pulmonary tuberculosis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation